The Development of English Syllabus Based on Hypnoteaching Method - Rois Rahmawan (Nuris Journal of Education and Islamic Studies, 2022)
Syllabus is very important for teachers, it is used by the teachers as reference before they do the teaching learning process, Syllabus is very flexible and contextual based on students' condition. Syllabus contain alternative for teachers when they teach. The teachers' creativity will rise when teachers understand the students' characters and their environments condition. To understand the students characters and their environments, researcher combines the syllabus with hypnotherapy sciences. In this study the researcher developed syllabus and hypnosis in hypnotherapy. Researcher combines between hypnosis technique and teaching techniques. This combination becollle the Hypnoteaching technique and applied in syllabus of K13. In Hypnoteaching teacher makes the classroom activity become more interesting and students have competence to motivate their self and other friends. To Inake this thesis focus on the discussion, the researcher developed the syllabus of' K1 3 based on the Hypnoteaching method. The researcher used Research and Delopement. The setting of this research was SMP Nurul Islam Ponpes Nurul Islam Pungging-Mojokerto and the subject of this study was English teacher of SMP Nurul Islam Ponpes Nurul Islam Pungging-Mojokerto. It is done because English teacher does not develop the syllabus mean while the students need the special treatment in English class. The researcher presented the result of this research that was gotten by using Guide interview, observation and checklist. In this syllabus development Teacher used technique of hypnotherapy and brings the students come to hypnosis condition in subconscious mind and students do not complicate to receive the information.